Surgeons' Experience In Breast Conserving Surgery: Does It Influence Surgical Margin? - Shahrun Niza AS; Ussof Eskaandar MH; Nani Harlina ML; Rohaizak M; Razrim Rahim (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2024)
Volume: 6 No: 1